Best practice guidelines on clinical management of acute attacks of porphyria and their complications. (May 2013) - Stein, Penelope; Badminton, Mike; Barth, Julian; Rees, David; Stewart, M Felicity
The British and Irish Porphyria Network guidelines describe best practice in the clinical assessment, investigation and management of acute porphyria attacks and their complications, including severe attacks with neuropathy. Acute attacks of porphyria may occur in acute intermittent porphyria (AIP), variegate porphyria (VP) and hereditary coproporphyria (HCP). Aminolaevulinic acid dehydratase deficiency porphyria (ADP) is a very rare autosomal recessive porphyria; only six cases substantiated by mutation analysis have yet been described in the literature. Urinary porphobilinogen (PBG) is always raised in an acute attack due to AIP, VP or HCP and this analysis is essential to confirm the diagnosis. A positive result in a qualitative or semi-quantitative screening test must be followed by PBG quantitation at the earliest opportunity. However in a severely ill patient, treatment should not be delayed. Removal of precipitating factors, effective analgesia and control of symptoms with safe medication, attention to nutrition and fluid balance are essential. The indications for use of intravenous haem arginate are set out, together with advice on its administration. A small proportion of acute porphyria patients develop recurrent attacks and management options that may be considered include gonadotrophin-releasing hormone analogues, 'prophylactic' regular haem arginate infusion or ultimately, liver transplantation.